The Widely Conserved ebo Cluster Is Involved in Precursor Transport to the Periplasm during Scytonemin Synthesis in Nostoc punctiforme - Kevin Klicki (American Society for Microbiology, 2018)
ABSTRACT Scytonemin is a dimeric indole-phenol sunscreen synthesized by some cyanobacteria under conditions of exposure to UVA radiation. While its biosynthetic pathway has been elucidated only partially, comparative genomics reveals that the scytonemin operon often contains a cluster of five highly conserved genes (ebo cluster) of unknown function that is widespread and conserved among several bacterial and algal phyla. We sought to elucidate the function of the ebo cluster in the cyanobacterium Nostoc punctiforme by constructing and analyzing in-frame deletion mutants (one for each ebo gene and one for the entire cluster). Under conditions of UVA induction, all ebo mutants were scytoneminless, and all accumulated a single compound, the scytonemin monomer, clearly implicating all ebo genes in scytonemin production. We showed that the scytonemin monomer also accumulated in an induced deletion mutant of scyE, a non-ebo scytonemin gene whose product is demonstrably targeted to the periplasm. Confocal autofluorescence microscopy revealed that the accumulation was confined to the cytoplasm in all ebo mutants but that that was not the case in the scyE deletion, with an intact ebo cluster, where the scytonemin monomer was also excreted to the periplasm. The results implicate the ebo cluster in the export of the scytonemin monomer to the periplasm for final oxidative dimerization by ScyE. By extension, the ebo gene cluster may play similar roles in metabolite translocation across many bacterial phyla. We discuss potential mechanisms for such a role on the basis of structural and phylogenetic considerations of the ebo proteins. IMPORTANCE Elucidating the biochemical and genetic basis of scytonemin constitutes an interesting challenge because of its unique structure and the unusual fact that it is partially synthesized in the periplasmic space. Our work points to the ebo gene cluster, associated with the scytonemin operon of cyanobacteria, as being responsible for the excretion of scytonemin intermediates from the cytoplasm into the periplasm during biosynthesis. Few conserved systems have been described that facilitate the membrane translocation of small molecules. Because the ebo cluster is well conserved among a large diversity of bacteria and algae and yet insights into its potential function are lacking, our findings suggest that translocation of small molecules across the plasma membrane may be its generic role across microbes.